Assessment of Factors Influencing Retention of Teachers in Private Secondary Schools in Nakuru Sub County, Kenya - Malala, Ali A.; Waiganjo, Maina; Ragama, Philip (KABARAK UNIVERSITY, 2018)
The purpose of the study was to assess the factors influencing teacher turnover in private secondary schools in Nakuru Sub County. The objectives of this study were to assess the extent to which remuneration and Organizational culture contribute to teacher turnover in Private secondary schools in Nakuru Sub County. The study was guided by the Herzberg’s motivation theory and Vroom’s Expectancy theory. Descriptive survey research design was used. Stratified sampling was used to select a total of 18 private secondary schools and purposive sampling was used to pick 116 teachers out of a total population of 19 schools and 238 teachers. Primary data was collected by administering pretested structured questionnaires to respondents and analyzed using descriptive and inferential statistical techniques. The findings indicate that organizational culture has no significant influence on turnover of teachers in private secondary schools in Nakuru Sub County ( -0.137). Remuneration was found to have significant influence on teacher turnover in private secondary schools in Nakuru Sub County (0.442**). The study recommended that Turnover rate should be monitored and considered important in policy formulation regarding Human Resource factors and organizational factors since it will help management in retaining their teachers. Rewards and any benefits should be awarded on merit and experience in order to help in retention. The salaries of teachers need to be increased, which will not only retain the present teachers but also attract teachers from other schools as well. Schools should identify those benefits which have more influence on teacher retention. Furthermore, Schools need to revisit their present benefits package to identify those benefits which are not useful in order to replace them. Schools must conduct “stay” and “exit” interviews to understand as to why teachers choose to leave. This information will help in understanding the reasons why teachers leave and mitigate on them.
FULL TEXT
Keywords: Organizational Culture, Remuneration, Private Secondary School